Improving pregnancy care during the COVID-19 pandemic for pregnant women as vulnerable groups through assistance at the primary health care facility - Muhamad Jauhar; Kurniati Puji Lestari (Journal of Community Empowerment for Health, 2021)
Since it was found in December 2019, the novel Coronavirus Disease 2019 (COVID-19) has spread from Wuhan, China, to many other countries. A rapid increase of newly found cases was observed, and finally, in March 2020, the World Health Organization declared that Coronavirus Disease 2019 (COVID-19) is a global pandemic. As one of the vulnerable groups, pregnant women need to avoid COVID-19 transmission and maintain pregnancy health during the pandemic. This study aimed to improve pregnant women's self-management during the COVID-19 pandemic in the working area of the Padangsari Primary Health Care Services, Semarang City. The research method used an experimental design with a pre-posttest without a control group. A Smartphone application, namely "SEHARI," was used to share the module and video about pregnancy health guidelines; furthermore, various activities of this study included online classes for pregnant women via a WhatsApp group, pregnancy care behavior surveys, and evaluations. The offline activity was done in 1 meeting for 90-120 minutes, while online activities were done as needed. This study's target population was 22 pregnant women in  Puskesmas Padangsari Semarang City's working area selected by purposive sampling. A questionnaire was used that measures mother's behavior while engaging in pregnancy care and pregnancy examination screening. The validity and reliability tests showed that the instrument was valid and reliable to improve self-management of pregnant women during the COVID-19 pandemic in the working area. Bivariate data analysis of the independent variable's effect on the dependent variables used paired and independent t-tests to measure the self-management of pregnant women. The results showed that 50% of pregnant women fulfilled nutritional needs well, 59.1% of pregnant women did tetanus immunization, and 59.1% did pregnancy examinations and visits. Despite being a vulnerable group, pregnant women must continue their antenatal care during the pandemic with a strict health protocol. Specially designed online classes and Smartphone application can be used as media to deliver the essential health meassages so that pregnant women can still monitor their pregnancy health and have a way to bridge the existing programs in primary health care.